The Politics of Remembrance of Russia, Germany and the Concerns of Central and Eastern Europe. Comments on the Margin of a Russian-German History Textbook of the 20th Century - Banaszkiewicz, Mikołaj (Institute of National Remembrance Review, 2022)
Review: Россия – Германия. Вехи совместной истории в коллективной памяти. Vol. 3: XX century. Moscow: Институт всеобщей истории РАН, ООО “Интеграция: Образование и наука”, 400 pp., ISBN 9785904914080. This review article discusses a textbook on twentieth-century history, prepared in collaboration between German and Russian historians. The analysis of the publication’s content is set in a broader context-the place of Germany in Russia’s politics of remembrance (legislation, historical education). Of particular interest are the chapters whose caesuras are marked by the Revolution of 1917 and the end of Stalinism. The constitutive elements of the authors’ historical reflection, that are beliefs imposing the interpretation of events (the primacy of geopolitics, superpower), are indicated. The polemical remarks concern both the conceptual and methodological shortcomings of the textbook and the controversial interpretative approaches. The latter primarily concerns the genesis of World War II and the evaluation of the Yalta order. The above historiographical vision is contrasted with the collective memory of the national communities of Central and Eastern Europe.